Financing for development and the institutionalization of finance - Pérez, Caldentey Esteban ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Analyzes the financing for development using A.P. Thirwall's balance-of-payments constrained growth model.